2015
DOI: 10.1038/srep18603
|View full text |Cite
|
Sign up to set email alerts
|

Body part-centered and full body-centered peripersonal space representations

Abstract: Dedicated neural systems represent the space surrounding the body, termed Peripersonal space (PPS), by integrating visual or auditory stimuli occurring near the body with somatosensory information. As a behavioral proxy to PPS, we measured participants’ reaction time to tactile stimulation while task-irrelevant auditory or visual stimuli were presented at different distances from their body. In 7 experiments we delineated the critical distance at which auditory or visual stimuli boosted tactile processing on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

24
257
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 163 publications
(283 citation statements)
references
References 44 publications
24
257
2
Order By: Relevance
“…Critically, these reaction times within the approximated PPS are significantly faster than reaction times to unimodal tactile stimulation (i.e., when no visual stimulus is presented in conjunction with the tactile stimulus). Notably, when the stimulus instead recedes from the body, this sigmoidal relationship (usually) disappears (Canzoneri et al 2012;Teneggi et al 2013;Noel et al 2015;Serino et al 2015).This aligns with the aforementioned neurophysiological studies that have shown that neurons in the PPS network preferentially respond to stimuli approaching (in contrast to receding from) the body (Colby et al 1993;Graziano and Gross 1995;Fogassi et al 1996;Graziano et al 1997;Duhamel et al 1998).…”
Section: Introductionsupporting
confidence: 82%
See 4 more Smart Citations
“…Critically, these reaction times within the approximated PPS are significantly faster than reaction times to unimodal tactile stimulation (i.e., when no visual stimulus is presented in conjunction with the tactile stimulus). Notably, when the stimulus instead recedes from the body, this sigmoidal relationship (usually) disappears (Canzoneri et al 2012;Teneggi et al 2013;Noel et al 2015;Serino et al 2015).This aligns with the aforementioned neurophysiological studies that have shown that neurons in the PPS network preferentially respond to stimuli approaching (in contrast to receding from) the body (Colby et al 1993;Graziano and Gross 1995;Fogassi et al 1996;Graziano et al 1997;Duhamel et al 1998).…”
Section: Introductionsupporting
confidence: 82%
“…Experiment 1 To measure PPS boundaries, we used a visuo-tactile interaction task using dynamic visual stimuli [similar to the audio-visual interaction tasks in Canzoneri et al (2012) and Serino et al (2015) and to investigations in our lab: Kandula et al (2017) andde Haan et al (2016)]. The task and stimuli were designed and controlled by a custom MATLAB script.…”
Section: Visuotactile-interaction Taskmentioning
confidence: 99%
See 3 more Smart Citations